An Evaluation of Follow-Up Activities of Participants From an Urban Prostate Cancer Screening Event - Drake, Bettina F. (Am J Mens Health, 2019)
This study aims to evaluate follow-up activities completed by participants attending community prostate cancer (PCa) screening events. On-site surveys were collected from participants of 17 free PCa screening events from 2007 to 2011 in the St. Louis, MO metropolitan area. Follow-up action surveys were mailed to all on-site participants to assess medical (i.e., made an appointment with a doctor, got additional testing for PCa, made an appointment to be screened) and nonmedical activities (i.e., sought social support, health information-seeking, health behavior modifications) completed after the PCa screening event. Further, t tests and chi-square tests characterized participant information from the on-site survey and within each follow-up activity category for the mailed surveys. Among 1,088 on-site community PCa screening participants, the mean age was 50 years old, 94% were Black, and 30% responded to the mailed follow-up action survey. For the recorded follow-up activities, 65% of participants reported medically reported activities, of which “made an appointment to get a yearly physical” was the most common action (29%). Health behavior modifications were the most common nonmedically related activities (44%). Health information-seeking behaviors were the least reported follow-up action (22%). Men with higher incomes, married, with health insurance, and a primary care physician, most often participated in post-PSA screening activities, namely medically-related and social support activities. Understanding the most common activities completed by participants of a community PCa screening suggests the effectiveness of community events to re-engage underserved populations in the health-care system and provides insight on acceptable health promotion opportunities.